Studi Transmisi Hidayah di Kalangan Muslim Tionghoa Probolinggo (Perspektif Sosial dan Dakwah) - Humaisi, M. Syafiq (FKIP Universitas Wisnuwardhana, 2022)
This study aims to understand the existence of several factors that cause the transmission of the guidance of Allah SWT to a person. Hidayah is the full authority of Allah. This study used a qualitative method with a social perspective approach and da'wah so that life phenomena which are reflections of religious understanding can be understood directly from the perpetrators. The subject of this research is the Chinese Muslim community in Probolinggo. The results of the study showed that there is human involvement as a place for the transmission of guidance to emerge, including the discovery of several factors that accelerate, slow down and even condition the ups and downs of transmission of guidance in the form of religious conversion through the vow of reciting the shahadah. Therefore, the results of this study are expected to assist readers in determining concrete steps both methodologically, determining material and others in every understanding of Hidayah.